2008
DOI: 10.1111/j.1574-695x.2008.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete genomic characterization of an intertypic Sabin 3/Sabin 2 capsid recombinant

Abstract: The genetic properties of strain K/2002, isolated from fecal samples of a 7-month-old child who had received his first oral poliovirus vaccine (OPV) dose at the age of 3 months, are described. Preliminary sequencing characterization of isolate K/2002 revealed an S3/S2 recombination event at the 3' end of the VP1 coding region. A recombination event resulted in the introduction of six Sabin 2 amino acid residues in a Sabin 3 genomic background. Furthermore, mutations associated with loss of the attenuated pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
(58 reference statements)
2
17
1
3
Order By: Relevance
“…Alternatively, these discrepancies may have resulted from recombination events that had occurred within the capsid region. Such events are believed to be infrequent, probably because of the structural constraints imposed on virions, but previous studies have shown that they can occur in both PV species (14,15,23,36,39,60,67) and non-PV HEV species (16). Further analyses are under way to determine whether the discrepancies observed between the VP1 and VP2 methods for some samples can be attributed to such uncommon recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these discrepancies may have resulted from recombination events that had occurred within the capsid region. Such events are believed to be infrequent, probably because of the structural constraints imposed on virions, but previous studies have shown that they can occur in both PV species (14,15,23,36,39,60,67) and non-PV HEV species (16). Further analyses are under way to determine whether the discrepancies observed between the VP1 and VP2 methods for some samples can be attributed to such uncommon recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…The enterovirus recombination sites are located in the 59 non-coding region (NCR) and in the non-structural part of the 7500 nt genome in genes coding for proteins 2A, 2B, 2C and 3D. In addition, recombination in the capsid protein VP1 coding region has been shown Dedepsidis et al, 2008;Liu et al, 2000;Martin et al, 2002), as well as recombination in the VP2 protein coding gene (Kyriakopoulou et al, 2006). In addition to within-species recombination events, interspecies recombination has been suggested for HEV-B and HEV-C strains (Bolanaki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, more attention has been shifted toward nonpoliovirus enteroviruses, since it has been proven that many prototype strains, as well as Echo18 and CAV21 strains (1,20,35,36) are recombinants and there is more and more evidence for genetic exchange between circulating enteroviruses (30,35). Even though much progress has been made in studies of genetic exchange between enteroviruses, recombination junctions have been detected only in recombinant Sabin poliovirus strains (13,22).…”
Section: Discussionmentioning
confidence: 99%